Stiffness degradation of symmetric laminates with off-axis cracks and delamination: an analytical model. (15th March 2021) - Carraro, P.A.; Maragoni, L.; Quaresimin, M.
Abstract: Delamination is one of the main mechanisms involved in the fatigue damage evolution in multidirectional laminates made of unidirectional plies. Typically, delamination is induced by off-axis cracks, the tips of which terminate at the interface with the adjacent layers. One of the consequences of the presence of delamination is the degradation of the apparent laminate stiffness. In this work, an analytical model is proposed for predicting the entire stiffness matrix of a generic symmetric laminate with off-axis cracks in one ply (and its symmetric) and a delamination originated from their tips. The model is based on an optimal shear lag analysis of the laminate and estimates the laminate elastic properties as a function of the crack density and the delamination length. The only input data required are the ply elastic properties, the ply thickness and the lay-up. The model is successfully validated against experimental data and Finite Element analyses.